Platelets of Healthy Origins Promote Functional Improvement of Atherosclerotic Endothelial Progenitor Cells - Alexandru, Nicoleta; Safciuc, Florentina; Constantin, Alina; Nemecz, Miruna; Tanko, Gabriela; Filippi, Alexandru; Dragan, Emanuel; Bãdilã, Elisabeta; Georgescu, Adriana (Frontiers in Pharmacology, 2019)
The purpose was to evaluate the effect of platelets on functional properties of late endothelial progenitor cells (EPCs), in the direct co-culture conditions, and to investigate the involved mediators, in experimental induced atherosclerosis. The late EPCs obtained from two animal groups, hypertensive-hyperlipidemic (HH) and control (C) hamsters, named late EPCs-HH and late EPCs-C, were co-incubated with or without platelets isolated from both groups. Our results have showed that exposure to platelets from control animals: (i) promoted the late EPCs-C capacity to form colonies and capillary-like structures, and also to proliferate and migrate; (ii) improved the functional properties of late EPCs-HH; (iii) strengthened the direct binding EPCs-platelets; (iv) increased SDF-1 alfa, VEGF, PDGF and reduced CD40L, IL-1β,-6,-8 levels; and (v) enhanced miR-223 and IGF-1R expressions. Platelets from HH group diminished functional abilities for both EPC types and had opposite effects on these pro-angiogenic and pro-inflammatory molecules. Furthermore, testing the direct effect of miR-223 and IGF-1R on late EPCs disclosed that these molecular factors improve late EPC functional properties in atherosclerosis in terms of stimulation of the proliferation and migration abilities. In conclusion, in vitro exposure to platelets of healthy origins had a positive effect on functional properties of atherosclerotic late EPCs. The most likely candidates mediating EPC-platelet interaction can be SDF-1 alfa, VEGF, PDGF, CD40L, IL-1β,-6,-8, miR-223 and IGF-1R. The current study brings evidences that the presence of healthy origin platelets is of utmost importance on functional improvement of EPCs in atherosclerosis.